Sequential analysis of three-dimensional tibiofemoral relationship through anatomic anterior cruciate ligament reconstruction with gravity-assisted radiographic technique in prone position - Tachibana, Yuta (Asia Pac J Sports Med Arthrosc Rehabil Technol, 2019)
BACKGROUND/OBJECTIVES: It is important to restore the tibiofemoral relationship as well as the anterior knee laxity for more successful anterior cruciate ligament (ACL) reconstruction, since a residual abnormality in the tibiofemoral relationship would lead an abnormal stress on the articular cartilages/menisci and consequently increase the risk of osteoarthritis in the future. This study aimed to sequentially clarify the three-dimensional tibiofemoral relationship before and after anatomic anterior cruciate ligament (ACL) reconstruction under an anterior tibial load with a gravity-assisted radiographic technique in the prone position. METHODS: Fifteen patients with unilateral ACL injury participated in the study. Anatomic triple-bundle ACL reconstruction was performed using semitendinosus tendon autografts. During the computed tomography scans that were performed preoperatively, and those performed at 3 weeks and at 6 months postoperatively, the patients lay in the prone position with the knee flexed at 15°, wherein the calf weight could exert an anterior drawer force on the tibia due to gravity. Three-dimensional the tibial position relative to the femur were evaluated for each time point, followed by calculation of side-to-side differences in the parameters between the ACL-deficient/ACL-reconstructed knees and the contralateral intact knees. Seven healthy volunteers were enrolled in the control group and the side-to-side differences (right minus left) in these parameters were calculated. RESULTS: The tibia in the ACL-deficient knee was located anteriorly by 3.5 ± 1.1 mm and rotated internally by 2.4° ± 2.3°; these values were significantly larger than the corresponding values of −0.2 ± 1.5 mm and 0.1° ± 2.2° in the control group. However, at 3 weeks postoperatively, the tibia in the ACL-reconstructed knee was over-constrained as compared to that in the control group; it was located posteriorly by 2.5 ± 1.4 mm and rotated externally by 3.4° ± 3.4°. At 6 months postoperatively, no significant difference was observed in the tibial displacements/rotations between the patient and control groups. The side-to-side difference in the anterior knee laxity at the manual maximum anterior load was 0.1 ± 1.2 mm at 6 months postoperatively, with a significant improvement over the preoperative value of 7.4 ± 2.5 mm. CONCLUSIONS: Anatomic ACL reconstruction could restore not only the normal anterior knee laxity, but also the normal tibiofemoral relationship even under an anterior tibial load.